External Factors of Mothers in Exclusive Breastfeeding - Ningsih, Eka Sarofah; Wasi'ah, Asyaul; Inayah, Ajeng Dwi Firda (Interdisciplinary Social Studies, 2022)
Background: More than 40 percent of babies are introduced too early to breast milk companion foods, which is before they reach the age of 6 months, and the food given often does not meet the baby’s nutritional needs. The main problems with the use of breast milk in Indonesia are socio-cultural factors, lack of knowledge among pregnant women, families, and the public about the importance of breast milk, as well as the ranks of health workers who have not fully supported the Increased Breastfeeding (PP-ASI) by not providing Early Breastfeeding Initiation (IMD). Aim: To find out the external factors of mothers in exclusive breastfeeding in the handover village of Gresik Regency in 2021. Method: This research uses an analytical research design with a cross-sectional approach. The population in this study was mothers who had babies 7-12 months as many as 32 respondents and sampling in this study used the total population. Findings: Data analysis is performed using the Chi-square statistical test with Fisher Exact values in bivariate analysis and Regency Binary Logistic on multivariate analysis. Based on bivariate analysis with the statistical test Fisher Exact obtained ? = 0.000 on socio-cultural variables, ? = 0.010 on family support variables, and ? = 0.041 on health worker role variables. In the multivariate statistical test with Regency Binary Logistic, the value of sig = 0.015 in socio-culture, sig = 0.317 in family support, and sig = 0.273 in the role of health worker.